W obronie Gumika. Uwagi o "Bajkach funkcjonalistów" Tadeusza Skalskiego - Grabarczyk, Paweł (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2012)
The titular "Bandie" is a fictional creature devised by Tadeusz Skalski in his "Fairy Tales of Functionalism" (published in "Folia Philosophica" 24). It is supposed to be a reduction ad absurdum for the thesis of organizational invariance. I show that the argument works only because the though experiment Skalski uses is highly suggestive and that, contrary to Skalski's intentions, The Bandie is in fact quite a complex dynamic system.